2015
DOI: 10.1073/pnas.1510199112
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and postexposure efficacy of a potent human monoclonal antibody against MERS coronavirus

Abstract: Middle East Respiratory Syndrome (MERS) is a highly lethal pulmonary infection caused by a previously unidentified coronavirus (CoV), likely transmitted to humans by infected camels. There is no licensed vaccine or antiviral for MERS, therefore new prophylactic and therapeutic strategies to combat human infections are needed. In this study, we describe, for the first time, to our knowledge, the isolation of a potent MERS-CoV-neutralizing antibody from memory B cells of an infected individual. The antibody, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
235
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(245 citation statements)
references
References 32 publications
7
235
1
2
Order By: Relevance
“…The MERS-CoV RBD can elicit strong neutralizing antibody response and contains a critical neutralizing domain (Ma et al, 2014; Zhang et al, 2016), thus representing an ideal target for neutralizing mAb development. Notably, almost all reported MERS-CoV neutralizing mAbs including murine, human, and humanized mAbs, target the RBD (Corti et al, 2015; Du et al, 2014; Jiang et al, 2014; Li et al, 2015; Pascal et al, 2015; Tang et al., 2014; Ying et al, 2014; Yu et al, 2015). We previously developed an RBD-targeting murine neutralizing mAb, Mersmab1, and demonstrated its ability to neutralize MERS-CoV infection (Du et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MERS-CoV RBD can elicit strong neutralizing antibody response and contains a critical neutralizing domain (Ma et al, 2014; Zhang et al, 2016), thus representing an ideal target for neutralizing mAb development. Notably, almost all reported MERS-CoV neutralizing mAbs including murine, human, and humanized mAbs, target the RBD (Corti et al, 2015; Du et al, 2014; Jiang et al, 2014; Li et al, 2015; Pascal et al, 2015; Tang et al., 2014; Ying et al, 2014; Yu et al, 2015). We previously developed an RBD-targeting murine neutralizing mAb, Mersmab1, and demonstrated its ability to neutralize MERS-CoV infection (Du et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several neutralizing mAbs including LCA60, REGN3051, REGN3048, 4C2h, and m336 have been tested in vivo for their protective efficacy using non-lethal MERS-CoV challenge mouse or rabbit models (Corti et al, 2015; Li et al, 2015; Pascal et al, 2015; Houser et al, 2016). In this study, we evaluated the protective efficacy of hMS-1 in a lethal hDPP4-Tg mouse model, wherein we demonstrated that a single-dose (2 mg/kg) of hMS-1 completely protected hDPP4-Tg mice from a lethal challenge from MERS-CoV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While others, in an effort to develop a vaccine, involves extracting antibodies from a MERS-CoV survivor or seropositive camels. 40 However, these antibodies need time and investment, as they still to be evaluated in animal models.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…The use of PVs has been of crucial significance in the rapid pace of research into the Middle Eastern Respiratory syndrome (MERS) outbreak [8][9][10][11]. During the recent Ebola outbreak, PVs were successfully used in high-throughput screening studies that helped in the identification of potential antivirals and filovirus entry inhibitors [12][13][14] as well as in the study of the viral life cycle and virus receptor interaction [15].…”
Section: Pvs For Research and Therapeutic Agent Screeningmentioning
confidence: 99%